Enhanced dielectric and ferroelectric properties of Pb(Mg1/3Nb2/3)0.65Ti0.35O3ceramics by ZnO modification - Methee Promsawat (2018)
© 2014 The American Ceramic Society. Phase formation, microstructures, dielectric, and ferroelectric properties of ZnO-modified Pb(Mg1/3Nb2/3)0.65Ti0.35O3(PMNT/xZnO, where x = 0, 0.4, 2.0, 4.0, and 11.0 mol%) ceramics were studied. A coexistence of rhombohedral and tetragonal ferroelectric phases was observed at room temperature in all samples. The ceramics with the relative densities of 93%-95% were prepared. The modification by ZnO led to an increase in grain sizes of PMNT ceramics. The maximum dielectric constant of the pure PMNT ceramic was increased with x = 0.4-4.0 mol% ZnO doping, with the highest value being observed in the 2.0 mol% sample. Both the temperature at which the transition between rhombohedral and tetragonal ferroelectric phases took place (TR-T) and the Curie temperature of the ceramics tended to increase with increasing x. The ferroelectric properties were enhanced with increased remanent polarization and P(E) loop squareness in the compositions with x = 0.4-4.0 mol%. However, the ferroelectric properties were attenuated with x = 11.0 mol%.